Sulfated hydrogel matrices direct mitogenicity and maintenance of chondrocyte phenotype through activation of FGF signaling - Öztürk, Ece (Adv Funct Mater, 2016)
Deciphering the roles of chemical and physical features of the extracellular matrix (ECM) is vital for developing biomimetic materials with desired cellular responses in regenerative medicine. Here, we demonstrate that sulfation of biopolymers, mimicking the proteoglycans in native tissues, induces mitogenicity, chondrogenic phenotype, and suppresses catabolic activity of chondrocytes, a cell type that resides in a highly sulfated tissue. We show through tunable modification of alginate that increased sulfation of the microenvironment promotes FGF signaling-mediated proliferation of chondrocytes in a three-dimensional (3D) matrix independent of stiffness, swelling, and porosity. Furthermore, we show for the first time that a biomimetic hydrogel acts as a 3D signaling matrix to mediate a heparan sulfate/heparin-like interaction between FGF and its receptor leading to signaling cascades inducing cell proliferation, cartilage matrix production, and suppression of de-differentiation markers. Collectively, this study reveals important insights on mimicking the ECM to guide self-renewal of cells via manipulation of distinct signaling mechanisms.